Mechanical properties of fully martensite microstructure in Ti-6Al-4V alloy transformed from refined beta grains obtained by rapid heat treatment (RHT). (September 2017) - Chong, Yan; Bhattacharjee, Tilak; Yi, Jangho; Shibata, Akinobu; Tsuji, Nobuhiro
Abstract: Fully martensite microstructures transformed from refined β grains were obtained in a Ti-6Al-4V alloy by rapid heat treatment (RHT) into a single β phase region followed by water quenching. Ultrafine-grained equiaxed α   +   β microstructure obtained by hot compression of martensite was used as the starting microstructure for subsequent RHT. By increasing the heating rate from 10 °C/s to 50 °C/s, the resulting β grain size was refined from 40 μm to 8 μm, which was the smallest size of β reported so far. Both strength and ductility increased with decreasing the β grain size, which was attributed to the reduced micro-crack lengths by fractography analysis. Graphical abstract: